Cyber Terrorism and Cyber Security after 9/11: Case Study of Women in Pakistan - Warraich, Saqib Khan; Haider, Abeera; Ahmed, Umair (Annals of Human and Social Sciences, 2024)
The use of technologies for communication and information has made lives more interconnected today. Pakistan is progressing in the domain of technological innovations as well. The security of borders and space becomes an ongoing concern for Pakistani authorities, especially after 9/11. The goal of a comprehensive national security policy is lacking because Pakistan is ignoring the existential threat posed by cyberterrorism. Terrorists are gaining ground and jeopardizing numerous aspects of Pakistan's national security because of its poor cyber security. They are primarily looking out women to help in dissemination their ideologies. The study explores how terrorists, in particular, are radicalizing women through digital channels. Its primary emphasis is on how ISIS, BLA, and TTP operate online. The theory of social learning is applied. The study relies on a qualitative approach. Interviews are also conducted for data collection. Secondary sources, such as documents, newspapers, books, articles, and case studies are also analyzed. The study emphasizes on the women empowerment, awareness and education as well as the economic indepence of women.